2023
DOI: 10.1038/s42003-023-05057-w
|View full text |Cite
|
Sign up to set email alerts
|

Spermidine from arginine metabolism activates Nrf2 and inhibits kidney fibrosis

Abstract: Kidney metabolism may be greatly altered in chronic kidney disease. Here we report that arginine metabolism is the most altered in unilateral ureteral obstruction (UUO)-induced fibrosis of the kidneys in metabolomic analysis. Spermidine is the most increased metabolite of arginine. In human glomerulonephritis, the amount of spermidine shown by immunostaining is associated with the amount of fibrosis. In human proximal tubule cells, spermidine induces nuclear factor erythroid 2-related factor 2 (Nrf2). Subseque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…Previous studies have shown that the activation of the Nrf2 signaling pathway or the oxidative stress inhibitor NAC can increase telomerase expression and activity, preserve the number of primordial follicles, and improve the quality of oocytes in old mice [62,63]. Interestingly, spermidine can activate the Nrf2 signaling pathway, increase the activity of antioxidant enzymes and alleviate oxidative stress [37,64]. Therefore, spermidine may preserve telomere length and prevent ovarian aging by attenuating oxidative stress.…”
Section: Polyamines Alleviate Telomere Damage In Ovariesmentioning
confidence: 99%
“…Previous studies have shown that the activation of the Nrf2 signaling pathway or the oxidative stress inhibitor NAC can increase telomerase expression and activity, preserve the number of primordial follicles, and improve the quality of oocytes in old mice [62,63]. Interestingly, spermidine can activate the Nrf2 signaling pathway, increase the activity of antioxidant enzymes and alleviate oxidative stress [37,64]. Therefore, spermidine may preserve telomere length and prevent ovarian aging by attenuating oxidative stress.…”
Section: Polyamines Alleviate Telomere Damage In Ovariesmentioning
confidence: 99%